Conjugal chondropathy of the adolescent: general considerations and treatment guidelines - Pirotto, José M; ´Vargas, Hernán; Rodríguez Payret, Nery (Cirugía del Uruguay, 1973)
The paper refers to condropathy of joints, its complications and sequella and coxa vara in adolescents. Physiopathological hypothesis of slipping points to action of adductor and externa] rotating muscles, specially psoas. We base our treatment on above hypothesis;, adductors and psoas are abscissed and action of gravity is avoide.d in cases of non complicated condropathies with chronic slipping; this is followed by adjlstment and immobilization in plaster cast in acute and subacute cases. In the latter, when adjustment is not induced by manouvres, we perform myotomy followed by open field adjustment and immobilization in pelvipaedium plaster cast. Finally, we have treatment of coxa vara sequella through intratrochanteric tendimentional osteotomies, correcting varus and epiphyses retroversion, or through anterosuperior wedge cervical osteotomies following capsule graft on epiphyses to provide greater vascularization and prevent necrosis.